Decoding IPO: essays on influential factors for going public firms - Jardim, Micael Daher (2024)
Initial Public Offerings (IPOs) are significant events in the lifecycle of firms, serving as a gateway to public markets and broader investor bases. The decision to go public is influenced by a myriad of factors, each playing a crucial role in determining the success and performance of the IPO. This thesis delves into the complexities surrounding IPOs through a series of four comprehensive essays. Each essay explores different dimensions and influential factors that shape the outcomes of IPOs, contributing to the broader understanding of the IPO process and its implications. Anchored in the principles of signaling theory and market timing theory, the first essay investigates the relationship between underwriter prestige, IPO timing, and underpricing. It posits that the waiting time of an IPO is a critical factor that modulates the influence of underwriter prestige on underpricing. Through empirical analysis of 765 IPOs from the United States between 2011 and 2021, this study reveals that prestigious underwriters reduce the time to market, thereby reducing IPO underpricing. This essay provides a fresh perspective on the role of underwriter prestige, emphasizing the importance of market timing in optimizing IPO outcomes. The second essay examines the dynamics and influence of various stakeholders, including underwriters, auditors, and venture capitalists, on IPO performance. Focusing on IPO waiting time as a performance metric, the analysis uncovers how these stakeholders mitigate information asymmetry and contribute value beyond mere certification. This essay highlights the synergistic interactions between underwriters and venture capitalists, showing that their combined efforts significantly shorten IPO waiting times, thus enhancing the overall performance of the IPO. In the third essay, the focus shifts to the influence of venture capital presence and underwriter prestige on the sentiment expressed in IPO prospectuses. Guided by Impression Management Theory, this study explores how these factors impact investor perceptions and market outcomes through corporate communication strategies. Utilizing sentiment analysis and natural language processing, the findings indicate that venture capital presence and underwriter prestige positively affect the sentiment in IPO prospectuses, thereby influencing investor sentiment and enhancing IPO success. The fourth essay addresses the motivations behind pursuing foreign IPOs with a low likelihood of success. Through a detailed case study, this research investigates the strategic reasons behind such decisions, revealing that companies may use the IPO process as a signaling strategy to enhance market position and achieve other strategic objectives, in other words, entering a lost game to win other games played in parallel. Collectively, these essays provide a detailed examination of the factors influencing IPO outcomes, offering valuable insights for academics, practitioners, and policymakers. By decoding the complexities of the IPO process, this thesis contributes to the ongoing discourse on the optimal strategies and practices for going public, ultimately aiming to enhance the success and performance of firms in the public markets.